A beginner''s guide to carbon footprinting. Issue 1 (February 2012) - Williams, Ian; Kemp, Simon; Coello, Jonathan; Turner, David A; Wright, Laurence A
Carbon footprinting is one of the foremost methods available for quantifying anthropogenic environmental impacts and for helping tackle the threat of climate change. However, for any person undertaking a carbon footprinting analysis for the first time, they will almost certainly be struck by the broad array of definitions, approaches and terminology surrounding the field. This paper provides an introductory guide to some basic concepts in carbon footprinting for researchers and lay people interested in the area. Each stage of calculating a carbon footprint is considered and an introduction to the main methodologies is provided. The advantages and disadvantages of the various approaches are discussed and a rough framework of procedures is provided for the calculation of carbon footprints over a variety of subjects. Some general data sources are included and a glossary of key carbon footprinting terminology is available in supplementary data online.